Peningkatan Nilai Tambah Produk Kaos Polos melalui Pelatihan Tie Dye, Sablon, dan Bordir di Omah Oblong Jogja - Monalisa Monalisa; Revaldo Sihombing (Journal Economy and Currency Study (JECS), 2025)
Plain t-shirt products in small and medium-sized garment enterprises generally have low added value due to limited design differentiation and competition based mainly on price. This community service activity aimed to increase product added value through training in tie-dye, screen printing, and embroidery techniques at Omah Oblong Jogja. The methods included socialization, hands-on training sessions, and product evaluation. The training was conducted using a participatory approach to enhance participants’ technical skills and creativity in product design development. The results showed an improvement in participants’ ability to apply decorative textile techniques and produce more innovative products with higher market appeal. This activity contributed to improving product quality and increasing potential selling value, thereby strengthening the competitiveness of small enterprises in the creative industry sector.